Comparing petro-plastic and bioplastics supply chains: firm-level insights from the packaging industry - Danka, Ayoub; Saad, Shatina (Universiti Teknologi MARA Selangor, 2026)
This paper empirically compares supply chain practices between petro- plastic and bioplastic carrier-bag industries. It examines how sourcing, production, and distribution differ between established fossil-based chains and emerging compostable alternatives, and how these differences affect operational performance and transition feasibility. A qualitative comparative design was applied to two product-based supply chains, petro-plastic and bioplastic carrier bags—within the packaging industry. Evidence was derived from 17 semi-structured interviews with senior executives, factory managers, buyers, and association representatives across Europe, Southeast Asia, the Middle East, and Australasia. Data were analyzed using Braun and Clarke’s six-step thematic approach, identifying three core themes: sourcing practices, production configurations, and distribution structures. The results reveal pronounced divergences in sourcing stability, process maturity, and distribution scalability. Petro-plastic chains benefit from global supplier networks and cost efficiency, while bioplastic chains face supply constraints, quality variability, and regionalized logistics. Managers must reconfigure sourcing, production, and logistics capabilities to align efficiency with sustainability compliance. This study advances sustainable supply chain literature by providing firm-level comparative evidence on how material transitions reshape operational practices in the packaging sector.